Arrendamiento de inmuebles y su incidencia en el estudio de Precios de Transferencia en el Sector Avícola en La Libertad - 2012. - Moreno Rodríguez, Yesenia Natalí (2014)
Transfer Pricing in our country are of interest to taxpayers who meet the criteria for linkage and has a need to make a truthful disclosure statement. Therefore in this research emphasizes the leases of property for poultry companies of La Libertad, since they do not involve a purchase or a sale but a provision of service and there is complexity in determining a price for conductive mercy. That is why in this paper is as follows: the fulfillment of the criteria for linking North SAC Poultry Company and its affiliates, identifying transactions that are between them. Poultry companies have in common trading strategies involving specialization related companies, allowing them to offer a differentiated product, property leasing is one of the largest transactions of its kind (service delivery), behold the importance of determining the price for conductive mercy, for the Poultry company North SAC uses two factors to determine the price and according to the application of Transactional Net Margin method, the company adheres to the principle of arm's length.